Boron removal from seawater using date palm (Phoenix dactylifera) seed ash - Al.Haddabi, M.; Mushtaque, A.; Al.Jebri, Z.; Vuthaluru, Hari; Znad, Hussein; Al.Kindi, M. (Taylor & Francis Ltd., 2016)
The feasibility of date seed ash, a low-cost agricultural by-product in Oman, for the removal of boron from aqueous solution was investigated. The aim of this study was to understand the mechanism that governs boron removal from seawater using date seed ash as an adsorbent in batch adsorption experiments. The effects of adsorbent dose, contact time, and temperature on boron removal were tested. A surface study of the date seed ash was investigated using scanning electron microscope, energy-dispersive X-ray spectroscopy, and Fourier transform infrared. Thermogravimetric-analysis, specific area using Brunauer, Emmett and Teller method, and particle density were also obtained. The maximum removal efficiency of boron was around 47% at neutral pH. The application of date seed ash is a promising adsorbent for boron removal where it can be used as pretreatment before reverse osmosis desalination process. This will increase the stability of membranes, minimize the membrane scaling, and ultimately reduce the operating cost.